Dosimetric parameters and safety analysis of 3D-printing non-coplanar template-assisted interstitial brachytherapy for non-centrally recurrent cervical cancer - Wang, Cong; Cheng, Yan; Song, Yadong; Lei, Jia; Li, Yiqian; Li, Xia; Shi, Huirong (Frontiers in Oncology, 2023)
Introduction The prognosis of patients with non-central recurrent cervical cancer (NRCC) remains poor, and treatment options are limited. We aimed to explore the accuracy and safety of the 3D-printed non-coplanar template (3D-PNCT)-assisted 192Ir interstitial brachytherapy (ISBT) in the treatment of NRCC. Material and methods A total of 36 patients with NRCC who received 3D-PNCT-guided 192Ir ISBT in the First Affiliated Hospital of Zhengzhou University from January 2021 to July 2022 were included in this study. There were 36 3D-PNCTs that were designed and printed. The prescribed dose was 30–36 Gy, divided into five to six times, once a week. To evaluate whether the actual parameters were consistent with the preoperative design, the dosimetric parameters of pre- and postoperative treatment plans were compared, including dose of 90% high-risk clinical target volume (HR-CTV D90), volume percentage of 100% and 150% prescribed dose V100% and V150%, homogeneity index (HI), conformal index (CI), external index (EI), and dose received by 2 cm3 (D2cm3) of the rectum, colon, bladder, and ileum. The safety parameters including occurrence of bleeding, infection, pain, radiation enteritis, and radiation cystitis within 3 months after operation were recorded. Results All patients successfully completed the treatment and achieved the goals of the preoperative plan. There was no significant difference in the accuracy (HRCTVD90, V100%, EI, CI, and HI) and safety (D2cm3 of rectum, colon, bladder, and ileum) parameters of the postoperative plan compared with the preoperative plan (all p>0.05). Major side effects included bleeding at the puncture site (13.9%), postoperative pain (8.3%), acute radiation cystitis (13.9%), and radiation enteritis (19.4%). There were no serious perioperative complications and no grade 3–4 acute radiotherapy side effects. Conclusion 3D-PNCT-assisted 192Ir ISBT can be accurately and safely applied in the treatment of patients with NRCC.